Nematode community characteristics are associated to loggerhead turtle hatching success. (April 2020) - Tsiafouli, Maria A.; Dimitriadis, Charalampos; Boutsis, George; Mazaris, Antonios D.
Graphical abstract: Highlights: Loggerhead sea turtle nests offer an ephemeral habitat for the decomposer food web. Opportunistic bacterivorous nematodes are favored in the nests after egg hatching. The nematode Metabolic footprint is associated to dead loggerhead turtle hatchlings. High nematode diversity is associated to increased hatching success. Nematode community characteristics can help to assess and monitor sea turtle nests. Abstract: Nematodes represent an important group of animals in the decomposer food web, because of high diversities, abundances and functional roles supporting ecological processes, such as decomposition. They have been relatively well studied in numerous ecosystems, but have rather skipped attention in sea turtle nests at sandy shores, where a massive supply of nutrients is taking place after turtle egg hatching. Being excellent indicators of ecological functioning, we hypothesized that nematode community characteristics could be indicative of the ecological/functional state of sea turtle nests as affected by hatching characteristics (e.g. number of eggs, hatching success rate etc.). In our study, conducted in Zakynthos (Greece), we perform a pioneer in-depth analyses of nematode communities in Caretta caretta nests after egg hatching. We further explore whether turtle reproductive success, measured through a number of metrics reflecting stages and portion of alive/dead hatchlings, are linked to nematode community characteristics. We found 14 different nematode genera in total. Our analyses demonstrate that nematodes play a critical role in functionality and energy flow in sandy shore ecosystems and that sea turtle nests present an ephemeral micro-habitat hosting communities with specific characteristics. These include rather high nematode abundances and communities in early successional stages with a simple trophic structure, almost exclusively dominated by bacterivore nematodes (mostly opportunistic/c-p 1) and without top-down control. Variables either showing success or failure of hatching explained a large amount of variability of nematode community characteristics, supporting our hypothesis. The nematode Metabolic Footprint was strongly associated with the amount of dead hatchlings concentrated in the turtle nest. Nematode taxonomic diversity and richness were closely associated with an increased hatching success rate at nest level. Our findings can offer a base for developing a framework for comprehensive and standardized assessments of sea turtle nests that could ensure comparability of results over spatial or temporal scales in monitoring projects. Further research might show how increased diversity of nematode communities could be achieved so to improve reproduction output and success of loggerhead sea turtles.